Influence of antimicrobial sequence in the nursery on pig performance and economic return - Steidinger, M.U.; Dau, D.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 1,008 pigs (11.9 lb and 19 d of age) were used in a 42-d experiment to determine the influence of antibiotic regimen on growth performance and economic return. From d 0 to 10, pigs were fed diets containing either no antibiotic or Denagard at 35 g/ton and chlortetracycline at 400 g/ton (Denagard/CTC). From d 10 to 21, diets contained no medication, Denagard/CTC, Mecadox at 25 g/ton and Oxytetracycline at 400 g/ton, or Mecadox at 50 g/ton. From d 21 to 42, diets contained either no medication or Denagard/CTC. Adding Denagard/CTC to the diet from d 0 to 10 improved (P < 0.01) ADG, F/G, and margin over feed cost (MOFC). Adding antibiotics to the diet from d 10 to 21 improved (P < 0.01) ADG, ADFI, F/G, and MOFC. There were no differences between pigs fed diets containing Mecadox at 25 g/ton in combination with Oxytetracycline and pigs fed diets containing Mecadox at 50 g/ton. Pigs fed diets containing Denagard CTC tended (P < 0.09) to have greater ADG than pigs fed either diet containing Mecadox and tended (P < 0.07) to have improved F/G and MOFC than pigs fed diets containing Mecadox at 50 g/ton. Adding Denagard/CTC to the diet from d 21 to 42 improved (P < 0.05) ADG, ADFI, and F/G. Denagard/CTC also improved (P < 0.01) MOFC when gain was valued at $1.00/lb of gain. For the overall trial, adding antibiotics to the diet during any phase improved (P < 0.05) ADG. Overall feed efficiency was improved when antibiotics were added to the diet from d 0 to 10 and 21 to 42. Overall feed cost per pig was increased (P < 0.01) by the addition of antibiotics to the diet; however, the improvement in ADG resulted in no change in overall feed cost per pound of gain (P > 0.49). Overall, MOFC was increased when antibiotics were added to the diet from d 0 to 10 and d 10 to 21 when gain was valued at $0.50 or $1.00/lb and tended to increase (P < 0.06) when Denagard/CTC was added to the diet from d 21 to 42 when the extra gain was valued at $1.00/lb. These results demonstrate that adding antibiotics to the nursery diet improved pig performance and economical return on this commercial farm.
Keywords: Antimicrobial; Nursery pig; Swine